A new method for obtaining the magnetic shape anisotropy directly from electron tomography images - Radu, Cristian; Vlaicu, Ioana D.; Kuncser, Andrei C. (Beilstein Journal of Nanotechnology, 2022)
A new methodology to obtain magnetic information on magnetic nanoparticle (MNP) systems via electron tomography techniques is reported in this work. The new methodology is implemented in an under-development software package called Magn3t, written in Python and C++. A novel image-filtering technique that reduces the highly undesired diffraction effects in the tomography tilt-series has been also developed in order to increase the reliability of the correlations between morphology and magnetism. Using the Magn3t software, the magnetic shape anisotropy magnitude and direction of magnetite nanoparticles has been extracted for the first time directly from transmission electron tomography.
Keywords: electron tomography; magnetite; Python; shape anisotropy

(untitled) - Choi, K.; Jeong, G.; Hyun, S. K.; Nam, B.; Ko, T. K.; Lee, C. (J. Korean Phys. Soc., 2020)

(untitled) - Harju, H.; Pipitone, G.; Lefferts, L. (Front. Chem. (Lausanne, Switz.), 2020)

(untitled) - Chahal, S.; Kumar, A.; Kumar, P. (Appl. Nanosci., 2020)

(untitled) - Shahzad, F.; Nadeem, K.; Weber, J.; Krenn, H.; Knoll, P. (Mater. Res. Express, 2017)

(untitled) - Meng, Y.; Zhang, Z.; Yin, H.; Ma, T. (Micron, 2018)

(untitled) - Skelbæk-Pedersen, A.; Vilhelmsen, T.; Wallaert, V.; Rantanen, J. (J. Pharm. Sci., 2019)

(untitled) - Quinson, J.; Inaba, M.; Neumann, S.; Swane, A. A.; Bucher, J.; Simonsen, S. B.; Theil Kuhn, L.; Kirkensgaard, J. J. K.; Jensen, K. M. Ø.; Oezaslan, M.; Kunz, S.; Arenz, M. (ACS Catal., 2018)

(untitled) - Ajinkya, N.; Yu, X.; Kaithal, P.; Luo, H.; Somani, P.; Ramakrishna, S. (Materials, 2020)

(untitled) - Fisher, P.; Aumann, C.; Chia, K.; O'Halloran, N.; Chandra, S. (PLoS One, 2017)

(untitled) - Liu, W.; Zhou, M.; Kong, L. (Meas. Sci. Technol., 2009)

(untitled) - Alloyeau, D.; Ricolleau, C.; Oikawa, T.; Langlois, C.; Le Bouar, Y.; Loiseau, A. (Ultramicroscopy, 2009)

(untitled) - Stoner, E. C.; Wohlfarth, E. P. (Philos. Trans. R. Soc., A, 1948)

(untitled) - Lakshmanan, M. (Philos. Trans. R. Soc., A, 2011)

(untitled) - Crăciunescu, I.; Palade, P.; Iacob, N.; Ispas, G. M.; Stanciu, A. E.; Kuncser, V.; Turcu, R. P. (J. Phys. Chem. C, 2021)

(untitled) - Mamiya, H.; Fukumoto, H.; Cuya Huaman, J. L.; Suzuki, K.; Miyamura, H.; Balachandran, J. (ACS Nano, 2020)

Handbook of Magnetic Materials - Mohapatra, J.; Liu, J. P. (Rare-Earth-Free Permanent Magnets: The Past and Future, 2018)

(untitled) - Shao, Z.; Ren, S. (Nanoscale Adv., 2020)

(untitled) - Nayek, C.; Manna, K.; Imam, A. A.; Alqasrawi, A. Y.; Obaidat, I. M. (IOP Conf. Ser.: Mater. Sci. Eng., 2018)

(untitled) - Iacob, N.; Kuncser, A.; Comanescu, C.; Palade, P.; Kuncser, V. (J. Nanopart. Res., 2020)

(untitled) - Ó Conbhuí, P.; Williams, W.; Fabian, K.; Ridley, P.; Nagy, L.; Muxworthy, A. R. (Geochem., Geophys., Geosyst., 2018)

(untitled) - Nikolaisen, E. S.; Harrison, R. J.; Fabian, K.; McEnroe, S. A. (Geochem., Geophys., Geosyst., 2020)

(untitled) - Pryor, A., Jr; Yang, Y.; Rana, A.; Gallagher-Jones, M.; Zhou, J.; Lo, Y. H.; Melinte, G.; Chiu, W.; Rodriguez, J. A.; Miao, J. (Sci. Rep., 2017)

(untitled) - Otsu, N. (IEEE Trans., Syst., Man, Cybern., 1979)

(untitled) - Barnes, R.; Lehman, C.; Mulla, D. (Comput. Geosci., 2014)

(untitled) - Borgefors, G. (Comput. Vis. Image Understanding, 1996)

(untitled) - Vincent, L. (IEEE Trans. Image Process., 1993)

(untitled) - Kornilov, A. S.; Safonov, I. V. (J. Imaging, 2018)

(untitled) - Rebled, J. M.; Yedra, L.; Estradé, S.; Portillo, J.; Peiró, F. (Ultramicroscopy, 2011)

(untitled) - Hata, S.; Furukawa, H.; Gondo, T.; Hirakami, D.; Horii, N.; Ikeda, K.-I.; Kawamoto, K.; Kimura, K.; Matsumura, S.; Mitsuhara, M.; Miyazaki, H.; Miyazaki, S.; et al. (Microscopy (Oxford, U. K.), 2020)

Size Effects in Nanostructures, Basics and Applications - Kuncser, V.; Miu, L. (Engineering Magnetic Properties of Nanostructures via Size Effects and Interphase Interactions, 2014)

(untitled) - Levin, B. D. A.; Jiang, Y.; Padgett, E.; Waldon, S.; Quammen, C.; Harris, C.; Ayachit, U.; Hanwell, M.; Ercius, P.; Muller, D. A.; Hovden, R. (Microsc. Today, 2018)

(untitled) - Rueden, C. T.; Schindelin, J.; Hiner, M. C.; DeZonia, B. E.; Walter, A. E.; Arena, E. T.; Eliceiri, K. W. (BMC Bioinf., 2017)

(untitled) - Beleggia, M.; De Graef, M.; Millev, Y. (Philos. Mag., 2006)

(untitled) - Cronemeyer, D. C. (J. Appl. Phys., 1991)

(untitled) - Osborn, J. A. (Phys. Rev., 1945)